2022
DOI: 10.3389/fpsyg.2022.875161
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of the Curiosity in Classrooms Framework and Coding Protocol

Abstract: Curiosity is widely acknowledged as a crucial aspect of children’s development and as an important part of the learning process, with prior research showing associations between curiosity and achievement. Despite this evidence, there is little research on the development of curiosity or on promoting curiosity in school settings, and measures of curiosity promotion in the classroom are absent from the published literature. This article introduces the Curiosity in Classrooms (CiC) Framework coding protocol, a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 80 publications
3
26
0
1
Order By: Relevance
“…More than a century ago, Dewey (1916) posited that curiosity is a foundational disposition for both teachers and students when pursuing democratic education. Although the intuitive value of teacher curiosity is widely accepted (Jirout et al, 2018), the empirical literature pertaining to teacher curiosity lags. To fill this gap, Amorim Neto et al, (2022) sampled 518 U.S. teachers and found that teacher curiosity predicted their relationships with students, with relationships in Grades 6 to 8 particularly vulnerable to students' negative behavior, time constraints, large class sizes, family issues, and truancy.…”
Section: Teacher-student Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than a century ago, Dewey (1916) posited that curiosity is a foundational disposition for both teachers and students when pursuing democratic education. Although the intuitive value of teacher curiosity is widely accepted (Jirout et al, 2018), the empirical literature pertaining to teacher curiosity lags. To fill this gap, Amorim Neto et al, (2022) sampled 518 U.S. teachers and found that teacher curiosity predicted their relationships with students, with relationships in Grades 6 to 8 particularly vulnerable to students' negative behavior, time constraints, large class sizes, family issues, and truancy.…”
Section: Teacher-student Relationshipsmentioning
confidence: 99%
“…Panning out to varying workplace environments, curiosity is associated with job satisfaction, work engagement, healthy work relationships, and innovation in workplace performance . For students, curiosity is associated with important learning and social outcomes (Engel, 2011;Jirout et al, 2018). Further, curiosity might be a mechanism that students can use to leverage more just and supportive classrooms (Clark & Seider, 2017).…”
Section: Teacher-student Relationshipsmentioning
confidence: 99%
“…Shonstrom (2016) put forth that curiosity is a motivating force in discovery, exploration, adventure, and learning. It is the motive to know (Turner, 2014) and facilitates learning (Jirout et al, 2018). As curiosity involves a desire for seeking information in the absence of extrinsic reward (Klahr et al, 2013;Markey & Loewenstein, 2014), it is theoretically considered to be an integral and key component of intrinsic motivation (Gottfried, 1985;Gottfried et al, 2001Gottfried et al, , 2016Berlyne, 1971;Koballa & Glynn, 2007).…”
Section: Prediction 2 Curiositymentioning
confidence: 99%
“…It stands in contrast to a fixed mindset, or a belief that one’s intelligence and/or abilities are predetermined at birth due to luck or other innate factors (Dweck, 2006, 2016; Farrington et al, 2012). Having a growth mindset is associated with a wide variety of positive academic outcomes, including curiosity (Dickhäuser et al, 2016; Jirout, Vitiello, & Zumbrunn, 2018; Ng, 2018; Ritchhart, 2015); resilience (Dweck, 2006); and academic achievement (Claro, Paunesku, & Dweck, 2016; Haimovitz, Wormington, & Corpus, 2016; Sisk et al, 2018; West et al, 2016). Growth mindset research has often focused on the positive impact of brief psychological interventions, such as teaching students that their brains can grow larger, to help students shift from fixed to growth mindsets (e.g., Sarrasin et al, 2018; Yeager et al, 2019).…”
Section: Mindset Vs Behaviormentioning
confidence: 99%